Protective Roles of Endothelial AMP-Activated Protein Kinase Against Hypoxia-Induced Pulmonary Hypertension in Mice. Issue 2 (8th July 2016) - Omura, Junichi; Satoh, Kimio; Kikuchi, Nobuhiro; Satoh, Taijyu; Kurosawa, Ryo; Nogi, Masamichi; Otsuki, Tomohiro; Kozu, Katsuya; Numano, Kazuhiko; Suzuki, Kota; Sunamura, Shinichiro; Tatebe, Shunsuke; et al.
Abstract : Rationale: : Endothelial AMP-activated protein kinase (AMPK) plays an important role for vascular homeostasis, and its role is impaired by vascular inflammation. However, the role of endothelial AMPK in the pathogenesis of pulmonary arterial hypertension (PAH) remains to be elucidated. Objective: : To determine the role of endothelial AMPK in the development of PAH. Methods and Results: : Immunostaining showed that endothelial AMPK is downregulated in the pulmonary arteries of patients with PAH and hypoxia mouse model of pulmonary hypertension (PH). To elucidate the role of endothelial AMPK in PH, we used endothelial-specific AMPK-knockout mice ( eAMPK –/– ), which were exposed to hypoxia. Under normoxic condition, eAMPK –/– mice showed the normal morphology of pulmonary arteries compared with littermate controls ( eAMPK flox/flox ). In contrast, development of hypoxia-induced PH was accelerated in eAMPK –/– mice compared with controls. Furthermore, the exacerbation of PH in eAMPK –/– mice was accompanied by reduced endothelial function, upregulation of growth factors, and increased proliferation of pulmonary artery smooth muscle cells. Importantly, conditioned medium from endothelial cells promoted pulmonary artery smooth muscle cell proliferation, which was further enhanced by the treatment with AMPK inhibitor. Serum levels of inflammatory cytokines, including tumor necrosis factor-α and interferon-γ were significantly increased in patients with PAH compared with healthy controls. Consistently, endothelial AMPK and cell proliferation were significantly reduced by the treatment with serum from patients with PAH compared with controls. Importantly, long-term treatment with metformin, an AMPK activator, significantly attenuated hypoxia-induced PH in mice. Conclusions: : These results indicate that endothelial AMPK is a novel therapeutic target for the treatment of PAH. Abstract : Supplemental Digital Content is available in the text.